PengujianÂ ValiditasÂ KonstrukÂ Kriteria KecanduanÂ Internet - Soetjipto, Helly P. (Faculty of Psychology, Universitas Gadjah Mada, 2005)
ThisÂ researchÂ isÂ usedÂ toÂ exploreÂ theÂ internet addictionÂ conceptÂ whichÂ developedÂ byÂ Young whoÂ usedÂ theÂ internetÂ consumerÂ subjectÂ in Yogyakarta.Â 124Â subjectsÂ (63Â maleÂ aÂ andÂ Â 61 females)Â withinÂ 14â€35Â yearsÂ old,Â mostÂ ofÂ them wereÂ students,Â onlyÂ 3Â subjectsÂ whoÂ haveÂ worked. TheyÂ catagorizedÂ asÂ existingÂ userÂ Â becauseÂ Â they hadÂ theÂ criteriaÂ mentionedÂ byÂ GroholÂ (1999). ConfirmatoryÂ factorÂ analysisÂ becameÂ theÂ basic forÂ constructÂ validityÂ testing.Â AMOSÂ fifth versionÂ (studentÂ version)Â wasÂ usedÂ toÂ analyze theÂ data.Â ThereÂ areÂ 2Â factorsÂ whichÂ wasÂ testedÂ in structuralÂ equationÂ model,Â theyÂ areÂ mainÂ factor andÂ additionalÂ factor.Â Â TheÂ mainÂ factorÂ consists ofÂ Â 5Â itemsÂ andÂ additionalÂ Â factorÂ consistsÂ ofÂ 2 items. TheÂ resultÂ showedÂ thatÂ structuralÂ equation modelÂ didÂ notÂ haveÂ theÂ weaknessÂ whichÂ called HeywoodÂ Case,Â becauseÂ thereÂ wasÂ 1Â factor whichÂ consistsÂ ofÂ onlyÂ 2Â items.Â ThereÂ areÂ 2 modificationÂ suggested.Â TheÂ firstÂ modification modelÂ hasÂ discrepancyÂ indexÂ 9.782Â (p>0.05)Â and theÂ secondÂ modificationÂ modelÂ hasÂ 11.Â 452 (p>0.05). Keywords:Â constructÂ validity,Â internetÂ addiction